2021
DOI: 10.1016/j.jhepr.2021.100252
|View full text |Cite
|
Sign up to set email alerts
|

A hepatitis B virus transgenic mouse model with a conditional, recombinant, episomal genome

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Multiple identifications have confirmed that some functions of this rcccDNA are identical to those of naturally infection-formed cccDNA. These findings suggest that such rcccDNA substrates will likely facilitate future elucidations of chronic hepatitis B pathogenesis. …”
Section: Infection and Replication System Of Hbvmentioning
confidence: 99%
“…Multiple identifications have confirmed that some functions of this rcccDNA are identical to those of naturally infection-formed cccDNA. These findings suggest that such rcccDNA substrates will likely facilitate future elucidations of chronic hepatitis B pathogenesis. …”
Section: Infection and Replication System Of Hbvmentioning
confidence: 99%